5th Workshop on Child Computer Interaction (WOCCI 2016) 2016
DOI: 10.21437/wocci.2016-5
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of children's engagement using non-verbal features and ordinal learning

Abstract: In collaborative play, young children can exhibit different types of engagement. Some children are engaged with other children in the play activity while others are just looking. In this study, we investigated methods to automatically detect the children's levels of engagement in play settings using non-verbal vocal features. Rather than labelling the level of engagement in an absolute manner, as has frequently been done in previous related studies, we designed an annotation scheme that takes the order of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The authors reported only a slight improvement in the classifier recognition rate when using both behavioral and contextual features (94.79%) vs. when only behavioral features were utilized (93.75%), highlighting the key importance of the behavioral information. Kim et al (2016) investigated the use of vocal/acoustic features in determining child engagement in group interaction scenarios. The annotation scheme involves the giving and receiving of attention from other group members.…”
Section: Related Workmentioning
confidence: 99%
“…The authors reported only a slight improvement in the classifier recognition rate when using both behavioral and contextual features (94.79%) vs. when only behavioral features were utilized (93.75%), highlighting the key importance of the behavioral information. Kim et al (2016) investigated the use of vocal/acoustic features in determining child engagement in group interaction scenarios. The annotation scheme involves the giving and receiving of attention from other group members.…”
Section: Related Workmentioning
confidence: 99%
“…While individual speaking activity is not often informative to detect engagement, comprehensive behaviours such as speaker-changes, overlaps, and interruptions, demonstrated promising performances in the detection of engagement [28]. However, the performances of turn-taking features still remain doubtful in naturalistic settings where silent situations often occur.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Ranking SVM achieved significant improvement compared to conventional methods (e.g. classification) in speech emotion recognition and engagement detection [14,28]. However, none of these studies revealed limitations in silent situations which are common in child-child interactions.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations